Effects of pressure on the shear modulus, mass and thickness of the perfused porcine kidney. Issue 1 (2nd January 2015) - Helfenstein, C.; Gennisson, J.-L.; Tanter, M.; Beillas, P.
Abstract: Eleven fresh ex vivo porcine kidneys were perfused in the artery, vein and ureter with degassed Dulbecco׳s Modified Eagle Medium (DMEM). The effect of perfusion pressure was evaluated using ten different pressures combinations. The shear modulus of the tissues was estimated during perfusion using shear wave elastography. The organ weight change was measured by a digital scale and cameras were used to follow the changes of the dimensions after each pressure combination. The effect of perfusion on the weight and the thickness was non-reversible, whereas the effect on the shear modulus was reversible. Pressure was found to increase the average shear modulus in the cortex by as much as 73%. A pressure of 80 mmHg was needed to observe tissues shear modulus in the same range as in vivo tests ( G cortex =9.1 kPa, G medulla =8.5 kPa ex vivo versus G cortex =9.1 kPa, G medulla =8.7 kPa in vivo in Gennisson et al., 2012 ).